Relief seed assistance in Ethiopia - Bramel-Cox, P.J.; Nagoda, S.; Haugen, J.M.; Adugna, D.; Dejene, T.; Bekele, T.; Traedal, L.T. (2004)
For more than 30 years, the international community has been assisting Ethiopia in recovering from recurring disasters. A continual need for emergency agricultural assistance as a response to droughts, conflict snd famine has led many to question the effectiveness and sustainability of the current interventions and to search for alternative approaches. This paper discribes the approaches used for agricultural recovery in Ethopia, including problem diagnosis, design and implementation of interventions and evaluation. Furthermore, lessons from one specific case, based on fieldwork in East and West Hararghe are presented to assess the need for and appropriateness of the approach used.